Polska a Wspólnota Europejska - uwagi o współpracy i integracji gospodarczej - Winiarski, Bolesław (Wydział Prawa i Administracji UAM, 1994)
The article outlines the problems and difficulties arising in the process of co-operation and gradual economic integration of Poland and the European Community (or, currently: the European Union). These difficulties are related on the one hand to the maintaining by the EC of various trade barriers with regard to post-socialist countries, on the other hand to the incompatibility of Poland's economy with the EC standards, particularly those concerning the quality of products. The transitional period provided for in the Association Agreement is therefore very useful for broadly planned adjustment programs. The necessary strengthening of the competitiveness of Poland's economy may be obtained through an active industrial policy, as well as a subtle yet effective protection of the local market. The great challenge of the integration of the formerly separated parts of Europe can be met more easily with the help of a closer regional co-operation between the so-called Visegrad countries. Their current rivalry should thus be superseded by the co-ordination of actions aiming at integration with the EC.
Poland and the European Community - comments on economic cooperation and integration